2012
DOI: 10.3892/etm.2012.594
|View full text |Cite
|
Sign up to set email alerts
|

Neovascularization evaluated by CD105 correlates well with prognostic factors in breast cancers

Abstract: Abstract. Angiogenesis is critical for the growth, invasion and metastasis of cancers. Extensive neovascularization and tumor thrombus also correlate with a poor prognosis in breast cancer (BC). Although anti-angiogenic agents have been the therapies of choice for BC, in particular for triple-negative BCs, predictive markers for anti-angiogenic agents are lacking. Microvascular density (MVD) is commonly used to assess the neovascularization in tumors. Compared with pan-endothelial markers such as CD31, CD34 an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 34 publications
2
16
0
1
Order By: Relevance
“…Similar results were also demonstrated in other studies that MVD of CD31 did not correlate with clinical outcome (Honkoop et al, 1998;Mayers et al, 1998;Charpin et al, 2004). MVD determined by CD105 was found to predict disease free survival in patients with stage I and II diseases whereas only hormone receptors were found to correlate with overall survival in patients with stage III disease (Rau et al, 2012). However,vascular invasion was reported to be a significant prognostic factor in basal and triple negative breast cancer by univariate and multivariate analyses (Mohammed et al, 2011).…”
Section: Discussionsupporting
confidence: 82%
“…Similar results were also demonstrated in other studies that MVD of CD31 did not correlate with clinical outcome (Honkoop et al, 1998;Mayers et al, 1998;Charpin et al, 2004). MVD determined by CD105 was found to predict disease free survival in patients with stage I and II diseases whereas only hormone receptors were found to correlate with overall survival in patients with stage III disease (Rau et al, 2012). However,vascular invasion was reported to be a significant prognostic factor in basal and triple negative breast cancer by univariate and multivariate analyses (Mohammed et al, 2011).…”
Section: Discussionsupporting
confidence: 82%
“…Other typical markers of MSCs such as CD105 and CD146 could be present in this stromal cell type. Until now, the expression of CD105 and CD146 was described in endothelial progenitors [ 15 18 ] and pericytes [ 19 , 20 ]. Moreover, it was reported that the immunoexpression of microvessels containing CD105 or CD146-labeled endothelial cells is a marker of poor outcome in BC [ 15 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have demonstrated that Cu is associated with angiogenesis (40), which is important in the proliferation, invasion and metastasis of tumor cells (41,42). Therefore, based on the biological function of Cu in tumor progression, inhibition of angiogenesis by reducing the content of Cu in vivo may be developed as a novel strategy in cancer therapy (4,43).…”
Section: Cu and Cu-based Complexesmentioning
confidence: 99%